Curriculum Management Innovation in Realizing Excellent Elementary Schools - Amelia Kurnia; Sri Tutur Martaningsih; Dian Hidayati (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2025)
Abstract: Excellent schools are institutions that provide high-quality education through innovative curriculum management. However, not all primary schools can achieve the title of superior, including in the implementation of an innovative curriculum that is adaptive to the needs of students. This study aims to describe curriculum management innovation in realizing superior schools at SD Muhammadiyah Kadisoka. The research employed a descriptive qualitative approach, utilizing data collection techniques that included in-depth interviews, observation, and documentation. Informants were selected purposively, consisting of the principal, deputy head of curriculum, and three teachers. Data analysis was conducted using thematic analysis techniques that included coding and theme identification using ATLAS.ti software. The results showed that there were six main themes of curriculum management innovation, namely: innovation in evaluation, planning, implementation, curriculum organization, characteristics of excellent schools, and implementation challenges. Innovation is realized through curriculum reflection, collaboration among stakeholders, project-based learning approaches, learning differentiation, and supportive leadership. The main obstacles in implementing curriculum innovation include limited human resources, differences in curriculum between the office and the foundation, and low parental participation. This research contributes to the practice of innovation-based education management. Abstrak: Sekolah unggul adalah lembaga pendidikan yang menyediakan pendidikan berkualitas tinggi melalui pengelolaan kurikulum inovatif. Namun, tidak semua sekolah dasar dapat meraih predikat unggul, termasuk dalam implementasi kurikulum inovatif yang adaptif terhadap kebutuhan siswa. Penelitian ini bertujuan untuk menggambarkan inovasi pengelolaan kurikulum dalam mewujudkan sekolah unggul di SD Muhammadiyah Kadisoka. Penelitian ini menggunakan pendekatan kualitatif deskriptif, dengan teknik pengumpulan data yang meliputi wawancara mendalam, observasi, dan dokumentasi. Narasumber dipilih secara purposif, terdiri dari kepala sekolah, wakil kepala sekolah bidang kurikulum, dan tiga guru. Analisis data dilakukan menggunakan teknik analisis tematik yang meliputi pengkodean dan identifikasi tema menggunakan perangkat lunak ATLAS.ti. Hasil penelitian menunjukkan adanya enam tema utama inovasi manajemen kurikulum, yaitu: inovasi dalam evaluasi, perencanaan, implementasi, organisasi kurikulum, karakteristik sekolah unggul, dan tantangan implementasi. Inovasi diwujudkan melalui refleksi kurikulum, kolaborasi antar pemangku kepentingan, pendekatan pembelajaran berbasis proyek, diferensiasi pembelajaran, dan kepemimpinan yang mendukung. Hambatan utama dalam implementasi inovasi kurikulum meliputi keterbatasan sumber daya manusia, perbedaan kurikulum antara kantor dan yayasan, serta partisipasi orang tua yang rendah. Penelitian ini berkontribusi pada praktik manajemen pendidikan berbasis inovasi.